Locking up the AS1411 Aptamer with a Flanking Duplex: Towards an Improved Nucleolin-Targeting - André Miranda; Tiago Santos; Eric Largy; Carla Cruz (MDPI AG, 2021)
We have designed AS1411-N6, a derivative of the nucleolin (NCL)-binding aptamer AS1411, by adding six nucleotides to the 5'-end that are complementary to nucleotides at the 3'-end forcing it into a stem-loop structure. We evaluated by several biophysical techniques if AS1411-N6 can adopt one or more conformations, one of which allows NCL binding. We found a decrease of polymorphism of G-quadruplex (G4)-forming sequences comparing to AS1411 and the G4 formation in presence of K+ promotes the duplex folding. We also studied the binding properties of ligands TMPyP4, PhenDC3, PDS, 360A, and BRACO-19 in terms of stability, binding, topology maintenance of AS1411-N6, and NCL recognition. The melting experiments revealed promising stabilizer effects of PhenDC3, 360A, and TMPyP4, and the affinity calculations showed that 360A is the most prominent affinity ligand for AS1411-N6 and AS1411. The affinity determined between AS1411-N6 and NCL denoting a strong interaction and complex formation was assessed by PAGE in which the electrophoretic profile of AS1411-N6 showed bands of the dimeric form in the presence of the ligands and NCL.